The Influence of Social Media Usage, Internet Access, and Mobile Device Penetration on Social Interaction Quality among Adolescents in Indonesia - Ma'ruf, Fatmah; Pattiasina , Petrus Jacob; Setiawati, Rahmi; Camerling, Bella Claudia Frederika; Tuasela, Patrick Elisa (Eastasouth Institute, 2024)
This study investigates the influence of digital technology use on the quality of social interactions among adolescents in Indonesia. A quantitative research design was employed, utilizing a cross-sectional survey method to collect data from 180 adolescents. The survey instrument included Likert scale items measuring social media use, internet access, mobile device penetration, and the quality of social interactions. Structural Equation Modeling-Partial Least Squares (SEM-PLS) was used to analyze the data. The results revealed significant relationships between digital technology use and social interaction quality, with internet access, mobile device penetration, and social media usage exerting notable influences. The findings underscore the importance of promoting responsible digital habits and fostering meaningful social connections among adolescents in an increasingly digitalized world.